In vitro comparative study on the relevance of dental radiographies in detection of dental caries - Cornelia Bîcleşanu; Anamaria Florescu; Alexandru Burcea; Laur Iacob; Ştefan Ţigăeru Polihroniade; Denisa Danilă (Amaltea Medical Publishing House, 2019)
Radiography is the most used complementary means to diagnose dental caries. The aim of this study is to verify the expertise in radiography interpretation of a group of clinicians with different experience and training and also of a group of last year dental medicine students. Material and method. For this study, 18 extracted teeth were used on which proximal and occlusal demineralization, enamel preparations and dentin preparations were conducted. The teeth surfaces were then isolated with a nail polish except the preparations. Teeth were mounted in acrylic arcades and retro-alveolar radiographs, bite-wing radiographs and CBCT were performed. A questionnaire was developed that was sent online to the groups of dental clinicians and students. Results and discussion. Retro alveolar radiographs, proximal preparations: 49% of respondents did not diagnose demineralization, 42% caries in enamel and 16% caries in dentin. Occlusal preparations: 88% of the respondents did not diagnose demineralization, 60% of the caries in the enamel, all the respondents diagnosed the caries in the dentine. Bitewing radiographs, proximal preparations: 2% of respondents did not diagnose demineralization, 12% caries in enamel and 2% caries in dentin. Occlusal preparations: 90% of the respondents did not diagnose demineralization, 26% caries in enamel, all diagnosed caries in the dentine. At CBCT, proximal preparations: 26% of respondents did not diagnose demineralization, 26% caries in enamel and 20% caries in dentin. At the occlusal level, 22% of respondents did not diagnose demineralization, 8% caries in enamel and 8% caries in dentin. Conclusions. Following the radiological examinations conducted in this study, we can say that dental caries is diagnosed most quickly and correctly when they affect both the analysed proximal and occlusal surfaces with evolution in dentin.